2018
DOI: 10.1111/echo.14230
|View full text |Cite
|
Sign up to set email alerts
|

Incremental value of three‐dimensional transthoracic echocardiography over the two‐dimensional modality in the assessment of right heart compression and dysfunction produced by pectus excavatum

Abstract: The usefulness of two-dimensional transthoracic echocardiography (2DTTE) in the assessment of right heart compression and dysfunction produced by pectus excavatum chest wall deformity has been well described in the literature by several investigators. However, there is a paucity of reports describing incremental value of live/ real time three-dimensional transthoracic echocardiography (3DTTE) over the twodimensional technique in the evaluation of right heart function in these patients. We present a severe case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Improvement in cardiopulmonary status likely relates more to mitigation of right ventricular and right atrial compression, and possibly restoration of normal tricuspid annular anatomy, than correction of respiratory mechanics. 17 Among PC cases, 100% reported breathing improvement. This is consistent with previous reports of improvement in dyspnea after PC repair.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in cardiopulmonary status likely relates more to mitigation of right ventricular and right atrial compression, and possibly restoration of normal tricuspid annular anatomy, than correction of respiratory mechanics. 17 Among PC cases, 100% reported breathing improvement. This is consistent with previous reports of improvement in dyspnea after PC repair.…”
Section: Discussionmentioning
confidence: 99%
“…RVFAC was reduced at 19.39% (normal > 35%). Both RV GLS and RV free wall LS were also reduced measuring −16.53% (normal > −20%) and −16.55% (normal > −20%, Table , Figure A, Movie A), respectively . Given the submassive PE, UFT was initiated using the EkoSonic system (EKOS Corporation, MOSS S.p.A., Italy).…”
Section: Case Presentationmentioning
confidence: 99%
“…3,4 Recently developed (3D-STE) is a new ultrasonic diagnostic technology, which can obtain real-time ventricular total volume data by tracking the movement of myocardial spots in three-dimensional space, which can more accurately reflect the movement and strain of myocardial in all directions, and then comprehensively evaluate the overall systolic and diastolic function of myocardium. 5,6 Studies have shown that the strain index of 3D-STE can accurately evaluate the cardiac structure and function, and the overall area strain value is highly correlated with the severity of heart failure patients, which is one of the important indicators to evaluate the left ventricular systolic function of patients. 7,8 In addition, Shin et al have recently confirmed that three-dimensional strain value has a certain correlation with left ventricular end-diastolic pressure (LVEDP) of patients with coronary heart disease, which has certain reference value for evaluating left ventricular diastolic function of patients, however, this study did not cover CHD patients with different degrees of left ventricular diastolic dysfunction due to a small number of cases and a large number of diseases.…”
Section: Introductionmentioning
confidence: 99%